Uwe Johnsons Jahrestage als episches Erzählen der Moderne? Überlegungen im Anschluss an zwei Neuerscheinungen zum Erzählen in der Moderne und bei Uwe Johnson - van Laak, Lothar (Johnson-Jahrbuch 14)

“Ihr kennt die deutsche Seele nicht.” Geschichtskonzeption und filmischer Mythos in Fritz Langs Nibelungen - van Laak, Lothar (Antike und Mittelalter im Film. Konstruktion – Dokumentation – Projektion)

Ethik des Verstehens. Beiträge zur philosophischen und literarischen Hermeneutik

„Sängerpolemik und literarischer Selbstbezug in der Sangspruchdichtung: Aspekte der Streitkommunikation“ - Egidi, Margreth (ZfdPh 126)

Jean Piaget zur Einführung - Scharlau, Ingrid

Control of Attention by Nonconscious Information: Do Intentions Play a Role? - Scharlau, Ingrid (The 5th International Conference on Computer Vision Systems)
The present study explores the deployment of attention towards nonconscious information. It is both theoretically and empirically likely that the deployment of attention can be controlled by information which is not consciously registered (attentional priming), similar to the control of sensorimotor responses by nonconscious information (response priming). However, not much is known about the functional basis of attentional priming. The present experiment explore whether and how strongly intentions (current action pans) determine whether attention is allocated towards invisible information (so called direct parameter specification). The results demonstrate that intention-mediated control is possible, but it seems to break down easily, that is to provide a weak and non-robust type of control.
Keywords: visuo-spatial attention; metacontrast; masking; intention; direct parameter specification; perceptual latency; priming

Temporal processes in prime-mask interaction: Assessing perceptual consequences of masked information. - Scharlau, Ingrid (Advances in Cognitive Psychology)
Visual backward masking is frequently used to study the temporal dynamics of visual perception. These dynamics may include the temporal features of conscious percepts, as suggested, for instance, by the asynchronous-updating model (Neumann, 1982) and perceptual-retouch theory (Bachmann, 1994). These models predict that the perceptual latency of a visual backward mask is shorter than that of a like reference stimulus that was not preceded by a masked stimulus. The prediction has been confirmed by studies using temporal-order judgments: For certain asynchronies between mask and reference stimulus, temporal-order reversals are quite frequent (e.g. Scharlau, & Neumann, 2003a). However, it may be argued that these reversals were due to a response bias in favour of the mask rather than true temporal-perceptual effects. I introduce two measures for assessing latency effects that (1) are not prone to such a response bias, (2) allow to quantify the latency gain, and (3) extend the perceptual e
Keywords: temporal processes; prime mask interaction; perceptual consequences; masked information; visual backward masking; visual perception; Temporal Lobe; Visual Masking; Visual Perception; Consequence

Experiments on the Fehrer-Raab effect and the 'Weather Station Model' of visual backward masking. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The Fehrer-Raab effect (simple reaction time is unaffected by metacontrast masking of the test stimulus) seems to imply that a stimulus can trigger a voluntary reaction without reaching a conscious representation. However, it is also possible that the mask triggers the reaction, and that the masked test stimulus causes a focussing of attention from which processing of the mask profits, thus reaching conscious representation earlier. This is predicted by the Weather Station Model of visual masking. Three experiments tested this explanation. Experiment 1 showed that the masked test stimulus caused a temporal shift of the mask. Experiment 2 showed that the reaction in the Fehrer-Raab effect was not exclusively triggered by a conscious representation of the test stimulus: the mask was involved in evoking the reaction. Experiment 3 again revealed a temporal shift of the mask. However, the shift was only about half as large as the Fehrer-Raab effect. The psychometric functions suggested tha
Keywords: Fehrer-Raab effect; Weather Station Model; visual backward masking; reaction time; metacontrast masking; conscious representation; Cognition; Humans; Perceptual Masking; Pilot Projects; Psychology; Experimental; Psychometrics; Reaction Time; Visual Perception; Models; Reaction Time; Visual Contrast; Visual Masking

Visual attention and the mechanism of metacontrast. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The U-shaped metacontrast function may result from the superimposition of two monotonic components which reflect the effects of mechanisms similar to the peripheral and central processes suggested for backward pattern masking by Turvey (Psychol Rev 80:1-52, 1973). In an experiment using the disc-ring paradigm, it was demonstrated that the decreasing and increasing branches of the metacontrast function are differently affected by the exposure duration of the mask and a task-irrelevant stimulus (distractor) appearing in the contralateral visual hemifield. The phenomenal representation of masking is different for the two parts of the curve. It is suggested that masking in the second part of the masking function, but not in the first, is related to the control of visual attention. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual attention; metacontrast; backward pattern masking; monotonic components superimposition; Attention; Contrast Sensitivity; Humans; Judgment; Perceptual Masking; Visual Perception; Metacognition; Visual Contrast; Visual Attention; Visual Masking

Perceptual latency priming: A measure of attentional facilitation. - Scharlau, Ingrid (Psychological Research)
The present paper reviews recent research on perceptual latency priming (PLP). PLP is the relative latency advantage--earlier perception--of a visual stimulus that is preceded by another, masked stimulus at its location. The first stimulus attracts attention which accelerates perception of the second stimulus. This facilitation arises even if the first stimulus is visually backward-masked by the second one. The paper summarises research on temporal and spatial properties of PLP and the question whether intentions mediate shifts of attention to external events. Possible sources of PLP besides visuo-spatial attention are discussed. Finally, I give a review of feedforward and reentrant models of PLP and compare them to the empirical evidence. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: perceptual latency priming; attentional facilitation; visuospatial attention; visual backward masking; prior entry; Attention; Humans; Judgment; Reaction Time; Space Perception; Attention; Priming; Response Latency; Visual Masking; Visuospatial Ability

Die Beziehung zwischen Erwachsenen und ihren Eltern. Individuation und biographische Übergänge - Buhl, Heike M.

Emerging adulthood in Europe. Common traits and variability across five European countries - Buhl, Heike M.; Lanz, Margherita (Journal of Adolescent Research)
The fact that there is a specific age marking the emergence of adulthood in the United States has been well documented. The starting point for the studies included in this special issue is the assumption that the same can be said for European countries. Thus, a comparison of characteristics of emerging adulthood between different European countries was performed. In this special issue, contributions of scholars from five different European countries are taken as representative of different regions: Spain, Italy, Finland, Germany, and the Czech Republic. The efforts of the research are twofold. The first is to look at how the traditional markers of adulthood have changed and how the concept of adulthood is seen in the different countries. The second is to highlight the influence that the entrance into the working world and romantic partnership have on emerging adults and to detect the impact of the timing of entering adulthood on identity achievement. The results are presented here as different pathways that emerging adults follow to reach the same goal of mature adulthood.

Well-being and the child-parent relationship at the transition from university to work life - Buhl, Heike M. (Journal of Adolescent Research)
This longitudinal study addresses the impact of the transition from university to work life on emerging adults' well-being and their relationship with their parents. A sample of 102 German students attending their last year at the university (M = 25.44 years, SD = 2.61) completed a questionnaire. Among others, scales from the Network of Relationships Inventory and symptom checklists were administered. Four years later, 51 employed participants of the initial sample were contacted again. During the transition from university to work life, well-being and the relationship with their parents improved. Following a typological approach, two groups of emerging adults were revealed by means of cluster analyses. Well-being in one group increased, whereas well-being in the second group decreased. Group membership was predicted by sex, personality, and the child–parent relationship in university times.

zu Nigel Harkness et al. (Hg.): Birth and Death in Nineteenth-Century French Culture, Amsterdam - Schlieper, Hendrik (Romanische Forschungen 123.4, 2011)

Kristallisation als kulturelle Transformation. Stendhal, W.G. Sebald und das Problem der Wirklichkeitstreue - Öhlschläger, Claudia (Verschiebebahnhöfe der Erinnerung. Zum Werk W.G. Sebalds)

"Geistige Raumscheu". Bemerkungen zu Wilhelm Worringers Anthropologie der Abstraktion. - Öhlschläger, Claudia (Struktur, Figur, Kontur. Abstraktion in Kunst und Lebenswissenschaften)

"Unheimliche Heimat. Literarische Positionen und Reflexionen zur Psychologie des Exils" - Öhlschläger, Claudia (Gehetzt. Südfrankreich 1940 - Deutsche Literatur im Exil)

"Effet du réel". Strategie di costruzione dell ́illusione in W.G. Sebald - Öhlschläger, Claudia (Scritture dell ́immagine.)

Einleitung - Öhlschläger, Claudia (Wilhelm Worringer: Abstraktion und Einfühlung. Ein Beitrag zur Stilpsychologie)

OEconomie der Lüste. Konfigurationen des ‚plaisir’ in der galanten Anthropologie der Frühaufklärung (Etienne-Simon de Gamaches, Dupuy La Chapelle) - Steigerwald, Jörn (Physis und Norm. Neue Perspektiven der Anthropologie im 18. Jahrhundert)